Simon Dubnow's "new Judaism" : diaspora, nationalism and the world history of the Jews - Seltzer, Robert M. (Supplements to The Journal of Jewish Thought and Philosophy, 2014)
In this volume Robert Seltzer examines Simon Dubnow (1860-1941) as the most eminent East European Jewish historian of his day and a spokesperson for his people, setting out to define their identity in the future based on his understanding of their past. Rejecting Zionism and Jewish socialism espoused by contemporaries, he argued in "Letter on Old and New Judaism" that the Jews of the diaspora constituted a distinctive nationality deserving cultural autonomy in the liberal multi-national state he hoped would emerge in Russia. Seltzer traces the young Dubnow's personal encounter with European intellectual currents that led him from the traditional shtetl world to a non-religious conception of Jewishness that resonated beyond Tsarist Russia.